The role of student leadership in academic achievement: a pathway to framework development - D. Aquino, John Michael; San Luis, Christian P. (Institute of Advanced Engineering and Science, 2025)
Leadership is widely recognized in fostering personal development and academic achievement of every student. This study explores the relationship between leadership involvement and academic performance, identifying influencing factors, best practices, and a framework for development. Using a mixed-method approach with concurrent triangulation, 179 randomly selected undergraduate student leaders completed a validated survey analyzed through Spearman’s rank-order correlation, while 12 purposively selected participants underwent semi-structured interviews analyzed thematically. Findings show a strong positive correlation (rs=0.744, p<0.001) between leadership involvement and academic achievement. Leadership fosters skill development, personal growth, motivation, and support systems. Best practices include capacity-building programs, inclusivity, recognition, supportive structures, and collaboration. A structured framework was developed to systematically enhance and sustain student leadership’s role in academic excellence. Institutional application highlights the need for universities to integrate leadership development into academic programs through structured mentorship, faculty engagement, governance mechanisms, and policy support. Higher education institutions (HEIs) can optimize student leadership initiatives by providing resources, recognizing achievements, and fostering an inclusive environment that supports holistic growth. The findings have significant implications for higher education policies and practices, emphasizing that well-structured leadership programs cultivate future-ready individuals capable of excelling academically and beyond.